Strategi Pemasaran Produk Pepsodent dalam Meningkatkan Volume Penjualan PT. Unilever Tbk. Area Bandar Lampung - Melan Susanty Purnamasari; Aslami Lazuardi Fartana (Business Perspective Journal, 2021)
Pepsodent toothpaste products attract consumers from the physical side and benefits so that consumers get information from Pepsodent toothpaste products for consideration in purchasing decisions. Therefore, companies need to study and know consumer or community responses to Pepsodent toothpaste, factors that can fulfill consumer desires and how far the position of this product is in the minds of consumers.This study analyzes how the marketing strategy of Pepsodent toothpaste products in increasing the sales volume of PT. Unilever Tbk. Bandar Lampung area. The purpose of this study is to find out what strategies can be done to increase the sales volume of PT. Unilever Tbk. Bandar Lampung area with a descriptive-qualitative research method, the key informant in this study was a branch manager of PT. Unilever Tbk. Bandar Lampung area, agent and marketing of Pepsodent products PT. Unilever Tbk. Bandar Lampung area, while the informants in this study were regular consumers of Pepsodent Toothpaste products in Bandar Lampung. Keywords: marketing strategy, sales volume, product